Migration and educational aspirations: Another channel of brain gain? - Marcus Böhme (Kiel Institute for the World Economy (IfW), 2012)
International migration not only enables individuals to earn higher wages but also exposes them to new environments. The norms and values experienced at the destination country could change the behavior of the migrant but also of family members left behind. In this paper we argue that a brain gain could take place due to a change in educational aspirations of caregivers in migrant households. Using unique survey data from Moldova, we find that international migration raises parental aspirations in households located at the lower end of the human capital distribution. The identification of these effects relies on GDP growth shocks in the destination countries and migration networks. We conclude that aspirations are a highly relevant determinant of intergenerational human capital transfer and that even temporary international migration can shift human capital formation to a higher steady state by inducing higher educational aspirations of caregivers.
Keywords: D03; O12; I21; J61; 330; education; aspirations; migration; brain gain